INTERNET OF THINGS UNTUK MONITORING KONDISI AIR BUDIDAYA IKAN KELOMPOK ‘TUTUT JAYA’ KOTA MALANG - Fitriana, Nurin; Darmawan, Azhar Adi; Rahmawati, Mariana Fitri (Jurnal AbdiMas Nusa Mandiri, 2024)
This service aims to improve the skills and knowledge of catfish farmers in the "Tutut Jaya" group related to the use of IoT technology in water quality monitoring. Through the training and implementation of IoT technology, it is expected that farmers can monitor and manage water quality more efficiently, thus increasing the productivity and sustainability of catfish farming. The dedication was carried out at the Catfish Farming Group "Tutut Jaya" in Arjowinangun Village, Kedungkandang District, Malang City. The methods used include training, technology implementation, as well as monitoring and mentoring. Training was given to improve fish farmers' understanding of the importance of maintaining stable pH and water temperature. In addition, IoT technology was introduced to monitor water quality in real time, enabling rapid intervention against inappropriate water conditions. Data was obtained through surveys, interviews, and analysis of IoT sensors that measure water pH and temperature. The results of the research show a significant improvement in the quality of pond water, which contributes to the health and growth of catfish. The use of IoT technology also increases operational efficiency, reduces resource consumption, and increases catfish production. Partners show a high level of satisfaction with the application of technology and the training provided. In conclusion, the implementation of IoT technology in water quality monitoring proved to be effective in increasing the success of catfish farming, with the potential to be applied more widely in the fishing industry.